2022
DOI: 10.1021/acscatal.2c04735
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping Substrate-Binding Pocket of Leucine Dehydrogenase for Bidirectionally Accessing Structurally Diverse Substrates

Abstract: Steric hindrance modification-based pocket reshaping is an effective approach for enzyme–substrate acceptance evolution. However, previous studies were limited to using the unidirectional acceptance trait of bulky substrates as a measure of fitness. In this endeavor, we conducted steric hindrance modification-based bidirectional pocket reshaping of Exiguobacterium sibiricum leucine dehydrogenase (EsLeuDH) for elucidating the differences in the molecular mechanism of pocket steric hindrance on the adaptability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 59 publications
(98 reference statements)
0
16
0
Order By: Relevance
“…42 The appropriate pocket size is necessary for an enzyme to interact efficiently with ligands. 26 As shown in Figure 5A,B, the distance between residues S267 and S180 (d (S180 − S267) ), on either side of the BuLTTA active site pocket, was used as an indicator to evaluate changes in the active site pocket. The value of d (S180 − S267) was 1 Å shorter in mutant M4 than in the WT enzyme, suggesting that the active site pocket of M4 was smaller (fine-tuned and more conducive to stable ligand binding).…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…42 The appropriate pocket size is necessary for an enzyme to interact efficiently with ligands. 26 As shown in Figure 5A,B, the distance between residues S267 and S180 (d (S180 − S267) ), on either side of the BuLTTA active site pocket, was used as an indicator to evaluate changes in the active site pocket. The value of d (S180 − S267) was 1 Å shorter in mutant M4 than in the WT enzyme, suggesting that the active site pocket of M4 was smaller (fine-tuned and more conducive to stable ligand binding).…”
Section: ■ Resultsmentioning
confidence: 99%
“…25 Wu et al successfully reshaped the active site pocket of isoleucine dehydrogenase from Exiguobacterium sibiricum by analyzing its sequence conservation and the pocket size. 26 To date, engineering of LTTAs has mainly focused on directed evolution. 27 However, even with efficient high-throughput screening methods, the effort required is still relatively high (typically screening thousands of variants) compared to rational design.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the successful application of steric hindrance based rational design strategy in enzyme activity enhancement towards bulky substrates ( Li F. et al, 2022 ; Wang Z. et al, 2022 ; Wu et al, 2022 ). α-ketoglutarate (α-KG) is the natural substrate of glutamate dehydrogenase (GluDH).…”
Section: Rational Design Strategy Based On Steric Hindrancementioning
confidence: 99%
“…The design engineering of enzymes is a valuable tool for enhancing biocatalytic diversity. One method of expanding the enzyme substrate scope is by reshaping the substrate‐binding pocket (Sacchi et al, 2002; Wu et al, 2022). The usual case is saturation mutagenesis of residues at a certain distance from the substrate, which will not change the reaction mechanism of the enzyme.…”
Section: Introductionmentioning
confidence: 99%